Development of six novel microsatellite markers for the Chilean red alga Pyropia orbicularis - Pérez-Lara, Gabriel; Meynard, Andrés; Alvear, Paula; Bulboa-Contador, Cristian; Contreras-Porcia, Loretto (Revista de Biología Marina y Oceanografía, 2020)
Mariculture of edible Porphyra/Pyropia species, which are cosmopolitan red foliose algae, represent an important source of income for the pharmaceutical and food industries. In Chile, the most common alga of this complex is Pyropia orbicularis (Bangiales, Rhodophyta). Here we report 6 microsatellite markers obtained from P. orbicularis through a genomic library from 10 individuals of the gametophytic phase by next generation (Illumina) sequencing. Polymorphism analyses were done from 10 individuals of the conchocelis phase, revealing an allelic diversity ranging from three to six alleles per locus, and observed heterozygosity (HO) and expected heterozygosity (HE) ranging from 0.200 to 0.995, and 0.250 to 0.610, respectively. A large proportion of genetic variance (61%) in P. orbicularis was among individuals within population, and 39% genetic variance was among populations. Nonetheless, these results should be interpreted with caution; further research using larger sample sizes is required. These polymorphic markers could be useful in future studies on population genetic structure, for conservation and applied purposes.